Sistem Pendukung Keputusan Kesesuaian Lahan Tanaman Padi Menggunakan Metode AHP dan SAW - Siti Retno Wulandari; Hamdani Hamdani; Anindita Septiarini (UIN Sunan Kalijaga Yogyakarta, 2022)
Rice is one of the staple foods for most of the world's population. However, in planting rice, there are several things that must be considered, namely the aspect of land suitability. Errors in land determination can cause crop failure which results in reduced rice production. This system was built based on the website using the Analytical Hierarchy Process (AHP) method to calculate the weight of the criteria and the Simple Additive Weighting (SAW) method to determine the selection of land suitability for rice plants. In determining the suitability of paddy fields using 5 criteria, namely soil type, soil pH, rainfall, temperature, and irrigation waters. The purpose of this research is to assist farmers/farmer groups in selecting land. The results of this study indicate that the AHP and SAW methods have been successfully applied in the system with the results of land recommendations in the Sungai Kunjang sub-district with a preference value of 0,989.